Creating a New Staple: Capital, Technology, and Monopoly in British Columbia’s Resource Sector, 1901-1925 - Mouat, Jeremy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1990)
AbstractThis paper examines the mining industry of British Columbia, the province's leading staple during the period when the region was brought within the network of world trade. Specifically, it describes the emergence of zinc production as the most profitable sector of the industry, from the early 1900s through to the mid-1920s. A good deal of importance was attached to discovering some means of treating zinc ore in the early 1900s. Increasing amounts of zinc were being found in the silver-lead ore of eastern British Columbia. Zinc was seen as a contaminant, and smelters penalised mine-owners who shipped ore that was over 10 per cent zinc. The presence of zinc rendered relatively valuable ore (in terms of its silver and lead content) uneconomical. Concern over “the zinc problem” was such that, by 1905, the federal government, responding to the lobbying efforts of mine-owners, appointed a commission “to Investigate the Zinc Resources of British Columbia and the Conditions Affecting Their Exploitation”. During the next twenty years, mining companies in the Kootenays explored a number of different ways to overcome zinc's unfortunate impact upon the mining industry.These efforts to discover an adequate means to treat zinc ore illustrate the way in which technology and capital became the key ingredients of a distinctively new mining industry. The paper argues that the emergence of zinc mining reflected a fundamental restructuring of the industry, as the focus shifted from the discovery and exploitation of bonanza deposits of gold and silver to the less spectacular production of copper, lead, and zinc. Technology, economies of scale, and substantial capital investment were the hallmarks of the new industry. Not only was the industry profoundly altered — experiencing what other scholars have described as the second industrial revolution — but new vertically integrated companies displaced the traditional mining company.The paper describes the clearest example of this trend, outlining the early career of the Consolidated Mining and Smelting Company of Canada [Cominco], a subsidiary of the Canadian Pacific Railway. Cominco was able to put in place the necessary technology to tap its enormous lead-zinc deposit at Kimberley, and successfully treat zinc at its Trail refinery. Within two decades, and largely as a result of its ability to treat zinc, Cominco became the most profitable mining company ever to operate in British Columbia. The conclusion suggests some consequences of Cominco's ascendancy.